WASTEWATER SLUDGE AS AN ALTERNATIVE ENERGY RESOURCE: A REVIEW - Tetuko Kurniawan; Rijal Hakiki; Filson Maratur Sidjabat (Journal of Environmental Engineering and Waste Management, 2018)
In recent years, concerns regarding to wastewater sludge disposal have increased globally. Production of sludge has increased recently due to the growth of population. Wastewater sludge classified as a hazardous substance, it is not easy to dispose because of certain treatment is required. Typically, sludge is treated at secured landfill which its limited in availability and expensive. On the other hand, wastewater sludge originated from biological treatment contains organic substance that can be converted into alternative energy resources. A technology is needed that is able to reduce the volume of sludge and convert sludge into energy source. We present an overview of various technologies that can be used for conversion of sludge into energy resources. Those technologies are anaerobic digestion, pelletization, combustion, pyrolysis and gasification. Progress and challenges of each technology is presented in detail. A summary of sludge characteristic originated from different source will be discussed as well. Emissions and residues that determines the environmental impact is also considered. Referring to some previous research, it known that wastewater sludge, as unwanted product, has the potential to become future energy resource. This potential can only be used properly if the method of conversion are effective and efficient.